PERAN ILLUSION OF CONTROL, LITERASI KEUANGAN DAN BIAS OVERCONFIDENCE DALAM MEMPENGARUHI KEPUTUSAN INVESTASI DIPASAR MODAL PADA MAHASISWA DI JAKARTA BARAT - Siti Nurchayati; Didin Hikmah Perkasa (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to determine and analyze the role of illusion of control, financial literacy and overconfidence bias in influencing investment decisions in the capital market for students in West Jakarta. The research design uses causal quantitative methods, namely knowing the effect between the variables studied. The data collection tool uses a questionnaire that has been tested for validity and reliability which is distributed via googleform to students in West Jakarta. The population studied in this study were 100 Undira students. The sample used was 100 people using saturated sampling technique. Data analysis was carried out using Smart-PLS (Partial Least Square) through outer model testing, inner model and hypothesis testing. The first stage makes a research instrument on each variable to be studied. The second stage tests the instrument variable Illusion of Control, Financial Literacy, Overconfidence Bias and Investment Decisions. The results of the study state that illusion of control, financial literacy and overconvidence affect investment decisions for students in West Jakarta